Colloidal quantum dot solar cell power conversion efficiency optimization using analysis of current‐voltage characteristics and electrode contact imaging by lock‐in carrierography. (10th August 2017) - Hu, Lilei; Liu, Mengxia; Mandelis, Andreas; Melnikov, Alexander; Sargent, Edward H.
Abstract: Although the power conversion efficiency (PCE) of colloidal quantum dot solar cells (CQDSCs) has increased sharply, researchers are struggling with the lack of comprehensive device efficiency optimization strategies, which retards significant progress in CQDSC improvement. This paper addresses this critical issue through analyzing the impact of colloidal quantum dot (CQD) carrier hopping mobility, bandgap energy, illumination intensity, and electrode/CQD interface on device performance to develop a guiding criterion for CQDSC PCE optimization. This general strategy has been used for the successful fabrication of high‐efficiency CQDSCs yielding certified PCEs as high as 11.28 %. A major experimental finding of this work is that the widely used constant photocurrent density ( J ph ) assumption is invalid as J ph is external‐voltage dependent due to the low carrier hopping mobility. Furthermore, the theoretical model developed herein predicts the nonmonotonic dependence of CQDSC PCE on carrier hopping mobility and bandgap energy, which were also demonstrated with the high‐efficiency CQDSCs. These results constitute a revision basis of the widespread belief that higher mobility and lower bandgap energy correspond to a higher CQDSC efficiency. Furthermore, electrode/CQD interface‐dependent surface recombination velocities were investigated in the framework of our abovementioned theoretical model using lock‐in carrierography, a contactless, large‐area frequency‐domain photocarrier diffusion‐wave imaging methodology that elucidated the carrier collection process at the electrodes through open‐circuit voltage distribution imaging. Lock‐in carrierography eliminates the limitations of today's widely used small‐spot (<0.1 cm 2 ) testing methods which, however, raise questionable overall solar cell performance and stability estimations. Abstract : A colloidal quantum dot solar cell (CQDSC) efficiency optimization strategy was developed as a guiding criterion for high‐efficiency CQDSC fabrication. Voltage‐dependent photocurrents were observed for the high‐efficiency CQDSCs and ascribed to low carrier mobility‐enhanced carrier recombination. The theoretically demonstrated existence of optimized carrier mobility and bandgap energy for a maximized power conversion efficiency was validated experimentally in our state‐of‐the‐art CQDSCs. Large‐area lock‐in carrierography carrier diffusion‐wave imaging reveals contact lifetime variations at the electrode/colloidal quantum dot interface and correlates with solar efficiency.